Pengaruh Pembelajaran Akidah Akhlak terhadap Akhlak Karimah siswa kelas IX MTs Raudlatul Jannah Cijujung Kecamatan Sukaraja Kabupaten Bogor - Kurniati, Nia; Edy (STIT Sirojul Falah Bogor, 2024)
The development of science and technology is currently very rapid, marked by the emergence of AI (Artificial Intelligence) and IoT (Internet of Things), apart from being able to improve human welfare, it will also have a negative impact. As a bulwark for students' self-defense in facing various challenges of the times, students need to receive religious education so that they do not fall into bad things. Learning moral beliefs is one part of the field of Islamic religious education that can provide knowledge, appreciation and a strong will to practice good morals and avoid bad morals. The aim of this research is to determine the effect of learning moral beliefs on the morals of class IX students at MTs Raudlatul Jannah Cijujung, Sukaraja District, Bogor Regency. This research uses quantitative research methods to determine the effect of variable X on variable Y. The population in this research is class IX students at MTs Raudlatul Jannah Cijujung. This research sample was taken using non-probability sampling techniques with total sampling or saturated sampling. Samples were taken from the entire population, namely 25 respondents. The data collection techniques used in this research are library and field methods. The instrument in this research uses a Likert scale in checklist form. The research results show that calculating the person coefficient using the Product Moment formula obtained a correlation value of 0.824 at a significance level of 5% from the r table of 0.413. Meanwhile, based on the t test, the tcount value is 12.274 > ttable is 1.717, meaning tcount is greater than ttable, so it can be concluded that in this study Ha is accepted and H0 is rejected. This means that there is an influence of learning moral beliefs on students' morals.